Sins of transmission? Vatican radio's high-power antennas stand accused of causing cancer. - Hellemans, A.
Residents of Cesano and neighboring communities are concerned that the strong radio-frequency fields generated by Vatican Radio's high-power antennas may pose a health threat. To address this concern, the regional government commissioned an epidemiological study of leukemia incidence in the area around the disputed antennas. Results indicate that the incidence of childhood leukemia from 1987 to 1998 was twice the expected rate, but the actual numbers were very small. Like those of previous studies, however, the results were found inconclusive. Despite the lack of compelling results, experts nevertheless believe that research should continue since so many people are exposed. In the meantime, Cesano residents can, in principle, rest assured that they are in no great danger.
Keywords: RF radiation; Vatican Radio; Cancer; Epidemiological study; Exposure limits; Health hazard; High-power antennas; High-power radio transmitters; Leukemia incidence; Radiofrequency exposure